Aplikasi Fuzzy Logic Tsukamoto dalam Analisis Kecanduan Permainan Mobile Legends Bang Bang - Khoiri, Muhammad Imamul (Maliki Interdisciplinary Journal, 2024)
The development of games, especially mobile games, is currently very rapid. Games with simple, short, and accessible gameplay are played more often than more complex games. One of them is Mobile Legends: Bang Bang (MLBB), which has been downloaded more than 500 million times in 2024. This research uses the Tsukamoto fuzzy logic method to measure the level of player addiction to this game. Bang Bang (MLBB) belongs to students of the Mathematics Study Program, Maulana Malik Ibrahim Malang State Islamic University, class of 2021, with a total of 11 accounts actively playing in season 32. win rate or percentage of player wins, which shows how competitive and skilled the players are in the game. It is hoped that these three variables can provide a comprehensive picture of the playing patterns and motivations behind the activities of MLBB players. Data from several MLBB users was analyzed using the Tsukamoto fuzzy logic method and calculated to obtain accurate conclusions. From the 11 data analyzed, the results showed that 82% of players had moderate addiction and 18% had high addiction.